2019
DOI: 10.1177/1369433219895913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transverse clamping force on the tensile behavior of a novel pultruded carbon fiber–reinforced polymer joint: Fatigue test

Abstract: A novel pultruded carbon fiber–reinforced polymer connection technique for civil engineering that is called pre-tightened single tooth joint has been proven to have good static properties. To investigate the fatigue behavior of the joint, a series of laboratory experiments were carried out. The effects of load level and transverse clamping force on the fatigue behavior were estimated. Experimental results of this work implied that a fatigue life of 1 million as the maximum cyclic load is equal to approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They concluded that the joint loads increased with the increase in bolt torque. Gao et al 19 conducted experiments to examine the impacts of transverse clamping force on the fatigue performance of pultruded carbon-fiber-reinforced joints. Their results showed that an increase in clamping force could markedly enhance the fatigue life and fatigue limit strength of connections.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the joint loads increased with the increase in bolt torque. Gao et al 19 conducted experiments to examine the impacts of transverse clamping force on the fatigue performance of pultruded carbon-fiber-reinforced joints. Their results showed that an increase in clamping force could markedly enhance the fatigue life and fatigue limit strength of connections.…”
Section: Introductionmentioning
confidence: 99%